The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0204610
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension-targeted therapies in heart failure: A systematic review and meta-analysis

Abstract: BackgroundPulmonary hypertension (PH) due to left heart failure (HF) is the most common form of PH. However, treatment is unclear because there are conflicting results about safety and efficacy of PH-targeted therapies.ObjectivesTo assess the effects of PH-targeted therapy on exercise capacity in HF patients.MethodsMEDLINE, EMBASE and the Cochrane Library were searched from January 1990 to July 2017 for randomized controlled trials comparing PH-targeted therapies to conventional therapy in HF. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…An exploratory analysis suggested PDE5i may be associated with a decrease in cardiac hospitalizations in some patients with HF but not in patients with valvular disease. 29 These findings are consistent with our study despite differences in patient population (echo diagnosis of PH and inclusion of VHD with no mention of PVR in their SR). The authors also reported a significant increase in treatment discontinuation, with no mention in the subgroup population taking PDE5i.…”
Section: Discussionsupporting
confidence: 92%
“…An exploratory analysis suggested PDE5i may be associated with a decrease in cardiac hospitalizations in some patients with HF but not in patients with valvular disease. 29 These findings are consistent with our study despite differences in patient population (echo diagnosis of PH and inclusion of VHD with no mention of PVR in their SR). The authors also reported a significant increase in treatment discontinuation, with no mention in the subgroup population taking PDE5i.…”
Section: Discussionsupporting
confidence: 92%
“… 87 A meta‐analysis pooling the results of multiple PH‐targeted therapies such as PDE5 inhibitors, prostanoids, ERAs, and soluble guanylate cyclase stimulators has concluded that PDE5 inhibitors may improve exercise capacity in patients with LHD, but that all drug classes resulted in a higher risk for adverse events. 88 …”
Section: Treatmentsmentioning
confidence: 99%
“…In a small minority of IPAH patients who are deemed vasoreactive based on a positive acute vasodilator challenge and without severe RV dysfunction, calcium channel blockers are appropriate and safe to use in pregnancy [3•]. Importantly, PAH-targeted agents have not been shown to be of benefit and can be detrimental in PH due to left heart disease [69]. Therapy in this group should be directed toward optimization of left heart function.…”
Section: Targeted Pah Medical Therapymentioning
confidence: 99%